2004
DOI: 10.1097/01.tp.0000128325.48350.be
|View full text |Cite
|
Sign up to set email alerts
|

HSP-72 Expression in Pre-Transplant Donor Kidney Biopsies and Post-Transplant Outcome

Abstract: In experimental transplant models, upregulation of renal heat shock proteins (HSP) represents a new therapeutic tool to improve allograft survival. In this clinical study, we hypothesized that HSP-72 expression in pretransplant donor kidney biopsies predicts posttransplant outcome. Expression of HSP-72 in pretransplant biopsies was assessed by immunohistochemistry and in situ hybridization in 82 consecutive renal transplantations and clinical data were collected prospectively during the first six months posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Concerns have been expressed that Hsp70 may be induced following brain stem death, obviating the benefit of therapeutic upregulation. However, Hsp70 has been shown to be only basally expressed in the kidney before engraftment, and hemodynamic instability in donors and the process of organ recovery were not found to produce a measurable increase in Hsp70 (31). This supports a view that therapeutic Hsp70 induction remains potentially beneficial.…”
Section: Discussionmentioning
confidence: 76%
“…Concerns have been expressed that Hsp70 may be induced following brain stem death, obviating the benefit of therapeutic upregulation. However, Hsp70 has been shown to be only basally expressed in the kidney before engraftment, and hemodynamic instability in donors and the process of organ recovery were not found to produce a measurable increase in Hsp70 (31). This supports a view that therapeutic Hsp70 induction remains potentially beneficial.…”
Section: Discussionmentioning
confidence: 76%
“…There are only limited data on HSP in ischemic renal injury in the human system; however, upregulation of HSP-70 expression, mostly upon heat pretreatment, has been shown to confer resistance against subsequent injury in experimental models of ischemia and transplantation [48,59,60]. A recent clinical study compared the renal tubular expression of HSP-70 in donor kidneys to the subsequent clinical course [61]. Interestingly, HSP-70 expression was low regardless of pretransplant insults and posttransplant outcome [61,62].…”
Section: Hsp In Renal Transplantationmentioning
confidence: 97%
“…A recent clinical study compared the renal tubular expression of HSP-70 in donor kidneys to the subsequent clinical course [61]. Interestingly, HSP-70 expression was low regardless of pretransplant insults and posttransplant outcome [61,62]. After engraftment HSP-70 was detectable in the first urine produced by renal grafts in the immediate postoperative period [63].…”
Section: Hsp In Renal Transplantationmentioning
confidence: 99%
“…However, this has not been replicated in experimental data, and results from studies are ambiguous and have not shown any definitive protective effects. [24,25] Some studies have even shown unpredictable effects such as enhanced immunogenicity [26] which can be dangerous in a transplant setting.…”
Section: Role Of Hsp In Kidney Transplantationmentioning
confidence: 99%